The Assay of Blood Plasma’s Malondialdehyde (MDA) Activity in Alloxan-Induced Diabetic Rat Given Yellow Velvet Leaf Extract (Limnocharis flava) - Yithro Serang; Ainun Nur Hammi (JURNAL INFO KESEHATAN, 2020)
It has been well-known that Genjer or yellow velvet leaf (Limnocharis flava) has a potential as an alternative source to natural antioxidants. Antioxidants, such as flavonoids, alkaloids, phenols, tannins, and others are substances which can block the presence of free radicals coming into the body. It has also been examined to be beneficial in treating metabolic syndrome diseases such as diabetes, as it improves insulin’s performance. The objective of this study is to examine the antioxidant effect of yellow velvet leaf’s ethanolic extract (Limnocharis Flava) on blood plasma’s MDA activity in alloxan-induced diabetic rats (Rattus novergicus) in three different doses. The testing animals were randomly divided into five groups, each group consisted of 6 white rats. Group 1 was the negative control and given CMC Na 0.5%, while group 2 was a positive control and given glibenclamide 0.45 mg, group 3 was yellow velvet leaf’s ethanolic extract of 32.5 mg/kg, group 4 was yellow velvet leaf’s ethanolic extract of 65 mg/kg, group 5 was yellow velvet leaf’s ethanolic extract of 130 mg/kg. Previously, all groups were induced with alloxan through intra peritoneal injection. Ethanol extract was provided once on the day of 7th, 14th, and 21st. The observed parameters were blood plasma’s MDA activity in the alloxan-induced diabetic rats (Rattus novergicus). Blood plasma’s MDA activities were assessed by using Thiobarbituric Acid Reactive Substance (TBARs) method. Then, data were collected and analyzed by using One Way ANOVA followed by a Post hoc test. The results showed that the mean values of MDA levels in the testing groups of 1,2,3,4 and 5 were 9.30 ± 0.462, 2.17 ± 0.121, 6.11 ± 0.381, 4.07 ± 0.327, and 2.75 ± 0.121, respectively. One Way ANOVA test showed a significant difference in the blood plasma’s MDA levels among the groups (p = 0,000). It is concluded that the blood plasma’s MDA levels in alloxan-induced diabetic rats can be lowered by the yellow velvet leaf’s ethanolic extract (Limnocharis Flava). Therefore, it can be employed as a traditional treatment for diabetes.